Which Is More Reliable? ICP-OES vs AAS for Chromium and Lead Analysis in Heavy Metal Monitoring - Seerwan Fadhil Shawkat; Shimaa A Ahmed; Sumaira Nadeem (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to compare the accuracy and reliability of Inductively Coupled Plasma Optical Emission Spectroscopy and Atomic Absorption Spectrometry in analyzing heavy metal contents specifically lead (Pb) and chromium (Cr) in textile wastewater. Methodology: The study employed a descriptive experimental method using water samples collected from a river suspected of contamination by textile waste. Tools used include AAS (APHA.322 B-2005), ICP OES (IK/LEL-ITS/ICP), and various laboratory glassware. Sample preparation followed SNI 6989.57:2008, and analytical validation included precision, accuracy, linearity, LOD, and LOQ testing. Main Findings: Both methods showed acceptable validation values, with linear regression coefficients (R²) above 0.995. ICP OES and AAS demonstrated good precision (%RSD ≤ 2%) and recovery rates between 93%–105%. However, significant differences were found between the two instruments (p = 0.012). Pb and Cr concentrations at discharge points exceeded regulatory limits. Novelty/Originality of this study: This study presents a comparative evaluation of ICP OES and AAS in the context of environmental monitoring, providing essential insights into their suitability for detecting heavy metals in complex wastewater matrices.